PSIX-10 Self-selection of plant bioactive compounds by sheep in response to challenge infection with Haemonchus contortus. (7th December 2018) - Poli, C; Thornton, K; Legako, J; Bremm, C; Hampel, V; Hall, J; Ipharraguerre, I; Villalba, J
Abstract: Plant bioactives can potentially benefit herbivores through their effects on health and nutrition. The objective of this study was to determine the importance of antioxidant polyphenols and terpenes on the ability of lambs to self-select these compounds when challenged by a parasitic infection and the subsequent impact on their health and productivity. Thirty-five lambs were housed in individual pens and assigned to five treatment groups (7 animals/group), where they received: 1) A basal diet of beet pulp:soybean meal (90:10) (Control); 2) The same diet, but containing 0.3% of bioactive natural plant compounds extracted from grape, olive and pomegranate (AOX); 3) A simultaneous offer of the diets offered to the Control and AOX groups (Choice-Parasitized; CHP-1); 4) The Control diet, and when lambs developed a parasitic infection, the choice described for CHP-1 (CHP-2); and 5) The same choice as CHP-1, but animals did not experience a parasitic burden (Choice-Non-Parasitized; CHNP). Lambs, except CHNP, were dosed with 10, 000 L3 stage larvae of Haemonchus contortus. Results were analyzed as a completely randomized design with seven replications per treatment. Individual animal was considered the experimental unit. Infected lambs under choice treatments (CHP-1 and CHP-2) modified their feeding behavior in relation to the CHNP group as they increased their preference for the feed containing polyphenols and terpenes (P < 0.05), interpreted as a behavior aimed at increasing the likelihood of encountering medicinal compounds and nutrients in the environment that restore health. This change in behavior corresponded with an improvement in feed conversion efficiency (P < 0.05). However, an increased preference for the diet with added plant bioactives did not have an effect on parasitic burdens, hematological parameters, blood oxidation, or serum concentration of IgE.